2005
DOI: 10.1097/01.jnen.0000178445.33972.a9
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Stimulate the Invasiveness of Glioma Cells by Increasing the Activity of Metalloprotease-2

Abstract: Gliomas represent the most frequent type of human brain tumor, and their strong invasiveness is a significant clinical problem. Microglia, the immunocompetent cells of the brain, contribute significantly to the tumor and are potential interaction partners of the glioma cells. We studied the impact of the presence of microglia on tumor cell invasion in cultured brain slices. To selectively deplete microglia, the slices were treated with clodronate-filled liposomes. When glioma cells were injected into slices de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
268
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(285 citation statements)
references
References 29 publications
11
268
2
4
Order By: Relevance
“…To verify that the effect of MT1-MMP deletion on glioma growth is mediated by microglial cells, we depleted microglia from the organotypic slice as described earlier (8). We could confirm the previous observation that depletion of microglial cells leads to a reduction of glioma expansion (8) (Fig.…”
Section: Blocking the Mt1-mmp Expression By Shrna In Microglia Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…To verify that the effect of MT1-MMP deletion on glioma growth is mediated by microglial cells, we depleted microglia from the organotypic slice as described earlier (8). We could confirm the previous observation that depletion of microglial cells leads to a reduction of glioma expansion (8) (Fig.…”
Section: Blocking the Mt1-mmp Expression By Shrna In Microglia Resultssupporting
confidence: 70%
“…By applying clodronate-filled liposomes to cultured brain slices, microglial cells were completely abrogated whereas the other cell types were not affected (8). After injection of GFP-expressing GL261 cells into these slices, the glioma cells invaded into the parenchyma.…”
Section: Mt1-mmp Expression Is Associated With the Presence Of Microgmentioning
confidence: 90%
See 2 more Smart Citations
“…MMP-14 can activate inactive matrix metalloprotease-2 secreted by glioma cells and lead to the break down of the extracellular matrix. Results from in vitro studies support the idea that microglia can promote tumor invasion and growth (Bettinger et al, 2002;Markovic et al, 2005). Perhaps the most convincing evidence of the importance of microglia to glioma formation is from in vivo studies that have shown that tumor cell growth is inhibited in microglia-deficient glioma mouse models (Daginakatte and Gutmann, 2007;Markovic et al, 2009).…”
Section: Microgliamentioning
confidence: 86%